Authenticity in Relationships: A Moderating Factor in Stress Communication and Marital Satisfaction during the First Five Years of Marriage - Pambudi, Phoebe Ramadina; Ratnasari, Yudiana (Kuras Institute, 2024)
The first five years of marriage are filled with role transitions in an individual's life. Therefore, dyadic coping strategies, especially stress communication, are important for maintaining marital satisfaction. Personality traits such as authenticity also play a role in this dynamic. Authenticity affects how individuals are able to communicate openly about their stress, thereby also affecting how they feel about their marriage. Participants in this study are 1228 Indonesian citizens in the first five years of marriage. Stress communication was measured by Stress Communication dimension in Dyadic Coping Inventory (DCI), Authenticity was measured with Kernis-Goldman Authenticity Inventory Short Form (KGAI-SF), and Marital satisfaction was measured using Revised Dyadic Adjustment Scale (RDAS). Interestingly, the moderation analysis shows that authenticity plays a significantly negative moderating role in the relationship between stress communication and marital satisfaction in the first five years of marriage. This suggests that when individuals become too authentic in their relationship, the positive effect of stress communication on marital satisfaction is weakened.